A rare mediastinal tumor-fat-forming solitary fibrous tumor - Rai, Deependra Kr.; Thakur, Somesh; Kr., Abhisheka; Pandey, Sanjay (International Journal of Advances in Medicine, 2018)
Solitary fibrous tumor is uncommon spindle cell mediastinal tumor arising mainly from pleural surface. Authors discuss a clinic-radiological features of Fat forming SFT which is rare variant of SFT in 70yrs old male patients. Initially we kept differential of Liposarcoma, Lymphoma on clinico-radiologically features but later after histopathology and Immunohistochemistery turns out to be Solitary fibrous tumor. Here accurate classification is important as SFT classified as intermediate type (rarely malignant), require wide surgical excision with close follow-up.